PENINGKATAN PENGETAHUAN DAN KESADARAN REMAJA TENTANG PERILAKU HIDUP BERSIH DAN SEHAT MELALUI PERMAINAN ULAR TANGGA DI DESA PIPA PUTIH KABUPATEN OGAN ILIR - Arigo Saci, Muhammad Amin; Etrawati, Fenny; Rahmawaty, Annisa (Universitas Udayana, 2024)
This research aims to improve the understanding and behavior of teenagers regarding the implementation of Clean and Healthy Living Practices (PHBS) by using the snakes and ladders game as a supporting tool. The area, especially in Ogan Ilir Regency, especially Pipa Putih Village, has been chosen as a focus for reducing the stunting rate, which in 2022 will reach 24.9%. One of the factors that has been identified as a cause of stunting is an unclean environment, this is in line with previous research which emphasizes the importance of PHBS. The research method used was a quasi-experiment with one group as the research subject. The snakes and ladders game was chosen as an intervention tool to increase teenagers' understanding and attitudes towards PHBS. The study results showed a significant increase in adolescents' understanding after the intervention, although not statistically significant in attitudes. The snakes and ladders game is recognized as an effective tool in increasing teenagers' knowledge about PHBS, in line with the efforts of the government and related institutions to improve public health. The use of games as a medium in health education promises to make learning more enjoyable and increase learning motivation. It is hoped that this research can become a basis for developing a wider intervention program to improve PHBS in society, especially in groups of teenagers who have the potential to be agents of change. Keywords: PHBS., Stunting., Snakes and ladders game